Dynamic correlations and portfolio optimization in socially responsible investments: evidence from Indonesia and South Korea - Ana Iglesias-Casal; Carmen López-Andión; Mª Celia López-Penabad; José Manuel Maside-Sanfiz (Humanities & Social Sciences Communications)
Abstract This study contributes to the literature on socially responsible investing by examining the diversification potential of green bonds and futures for a commodities’ index, gold and treasury bonds, alongside the SRI-KEHATI Index and the Dow Jones Sustainability Korea Index (DJSKI) from 2014 to 2024. Asymmetric Dynamic Conditional Correlation (A-DCC) models with GJR-GARCH in conditional variance and out-of-sample analysis are employed to explore dynamic conditional correlations, optimal weights and hedge ratios for stocks portfolio that include the SRI-KEHATI Index or the DJSKI. Constructing portfolios with optimal weights proves to be more effective in risk reduction compared to the hedge ratio strategy. The portfolio with optimal weights containing commodities exhibited the highest risk-adjusted return for both countries during the pre-war COVID-19 pandemic period, while in the subsequent period, portfolios containing gold performed best. Our findings provide valuable insights for investors, portfolio and risk managers, policymakers and index managers, aiding in improved risk management and decision-making for optimal portfolio allocation.